Effect of Cs-Ion on the corrosion properties of implant materials - Murat Bi̇len; Zübeyde Özkan; İrem Balci; Uğur Gökmen; Sema Bilge Ocak (Nuclear Engineering and Technology)
Ti-6Al-4V alloy produced by additive manufacturing method and Ti-6Al-4V alloy coated with BN ceramic were analyzed in SRIM/TRIM Monte Carlo Simulation program at 662 keV energy using parameters such as displacement, ionization and phonon, which provide information about radiation damage, using Cs-ion. Post-production coating thicknesses were determined by taking SEM images of the produced samples. As a result of coating the Ti-6Al-4V alloy with BN, the ion range decreased from the target depth of 3067 Å to 2447 Å. The total amount of damage to the material after coating decreased by approximately 21.1 % ensuring less phonon formation of the implant material exposed to the same gamma energy through the coating process, its negative effect on corrosion resistance, which is important in implant materials, is reduced.